The effect of social interaction on academic performance: The moderating influence of cultural background - Alraggad, Abeer (Edelweiss Applied Science and Technology, 2025)
This study seeks to examine the impact of social interactions, including cooperation, containment, conflict, and competition, on a student's academic performance in Jordan. In addition, it aims to determine how the cultural context influences the associations between such social interactions and accomplishments. The data obtained from Zarqa University and the University of Jordan were used to carry out descriptive statistics on the demographic of the participants, as well as to assess the major variables. Social interactivity with culture as a moderating factor was analyzed using structural equation modeling with SmartPLS to examine the relationship between social interactions and academic performance. A reliability and validity test is conducted on the measurement model by taking into account factor loadings, composites, and average variances. The structural model tests the paths of the proposed hypotheses by estimating path coefficients, t-values, and R² values of the relationships. Ethical clearance is provided by the ethics boards of the two universities for data collection, which is conducted within 2-3 weeks using class or online surveys. This study provides evidence of how certain social interactions and cultural aspects affect performance in university education.